Economic profit estimation of tranmission system using novel contingency ranking with markov modelling - E. Sreeshobha; P.V.N. Prasad (Indonesian Journal of Electrical Engineering and Computer Science, 2020)
Technique to evaluate probability of occurrence of selected contingencies of 6 Bus Roy Billinton Test System (RBTS) and IEEE 9 Bus system by Markov modelling is presented in this paper. Obtained probabilities for selected contingencies are validated by comparing with binomial distribution based probabilities. Load flow analysis and performance index based contingency ranking of total elements of 6 bus RBTS and IEEE 9 Bus systems is simulated by Power System Simulation for Engineers (PSSE) software. Novel reliability evaluation technique which unify contingency ranking with Markov modeling is proposed for RBTS and extended to IEEE 9 Bus system. Accuracy, completeness and simple to implement are salient features of proposed novel reliability evaluation method. Reliability of RBTS and IEEE 9 Bus systems can be improved by incorporating Flexible Alternating Current Transmission Systems (FACTS) device. Improvement in the reliability and economic revenue of RBTS and IEEE 9 Bus systems due to Unified Power Flow Controller (UPFC) incorporation is evaluated.